Methods of study in the characteristics of elastomers' samples of mud motors at modeling the conditions of their operation - Epikhin A. V. Anton Vladimirovich; Barztaikin V. V.; Melnikov V. V.; Isaev E. D. Evgeniy Dmitrievich; Ulyanova O. S. Oksana Sergeevna (Well drilling, 2016)
Title screen